2005
DOI: 10.1080/13816810500229058
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic Aspects of GAPO Syndrome: Case Report and Review

Abstract: This paper reports on a 36-year-old woman with GAPO syndrome, a rare autosomal recessive condition characterized by growth retardation (G), alopecia (A), pseudoanodontia (P), and optic atrophy (O). Her parents are consanguineous and one of her sisters is also affected. Since the first description by Anderson and Pindborg in 1947, 27 individuals have been reported with this diagnosis. They were from at least 19 different families (four of them from Brazil, including the present one), suggesting a founder effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…The increase in extracellular components can be due to different mechanisms causing either overproduction or decreased breakdown of one or more of the components in the matrix. As pointed out by Rim and Marques-de-Faria [2005], microscopic examination performed at the autopsy of one of the patients of Wajntal et al [1990] showed increase of an …”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The increase in extracellular components can be due to different mechanisms causing either overproduction or decreased breakdown of one or more of the components in the matrix. As pointed out by Rim and Marques-de-Faria [2005], microscopic examination performed at the autopsy of one of the patients of Wajntal et al [1990] showed increase of an …”
Section: Discussionmentioning
confidence: 91%
“…It is possible that the optic atrophy, found in five patients, is secondary to the nerve constriction, since there is evidence that thickening of the dura mater surrounding the optic nerve constriction occurred in an eventual optic atrophy [Wajntal et al, 1990;Ilker et al, 1999]. Other eye manifestations have been documented, such as strabismus, megalocornea, bilateral keratoconus, nystagmus, ptosis, glaucoma, and abnormal pattern visual evoked response [Meguid et al, 1997;Rim and Marques-de-Faria, 2005]. Goucha et al…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although distinctive facial features characterized by peculiar geriatric look with frontal bossing, midfacial hypoplasia, and the absence of eyebrows, eyelashes and hair aid the clinical diagnosis of GAPO syndrome, most other features described in these patients are not consistent. Among these, pulmonary hypertension, glaucoma, vestibular dysfunction, umbilical hernia, and dilated cardiomyopathy were reported [Rim and Marques‐de‐Faria, ; Demirgunes et al, ; Kocabay and Mert, ; Rapsomaniki et al, ]. Craniovascular venous abnormalities are limited to few reports, which include venous scalp malformations, dilatation of the scalp veins, and narrowing or agenesis of the sigmoid sinus and jugular vein [Moriya et al, ; Goucha et al, ; Castrillon‐Oberndorfer et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…S ir —GAPO syndrome, a rare clinical entity, has been associated with Growth retardation, Alopecia, Pseudoanodontia and Optic atrophy (1). GAPO syndrome may be associated with umbilical hernia, dilated cardiomyopathy, pulmonary hypertension, intracranial vascular malformations, glaucoma and keratoconus (2–6). A total of only 30 cases have been reported till date (1).…”
mentioning
confidence: 99%